Aulas de educação física na perspectiva do currículo cultural: tecendo caminhos com o futebol - Munhoz, Janaina de Freitas (2024)
Physical Education in Brazilian schools has changed over the years, as has the society to which it belongs. Initially it was characterized as an activity and, over the years with discussions, disputes, mistakes and successes, it arrived, in the 1980s, in the so-called “renovating movement”, seeking to insert reflections on the practice. At the beginning of the 21st century, with post-critical theories, the Cultural Curriculum of Physical Education (CCEF) emerged, which is anchored in the cultural diversity of society and school, seeking work alternatives that respect and exalt differences. Given the above, the present work aimed to analyze a teaching proposal from the perspective of the CCEF in the early years of elementary school. Qualitative research with participant characteristics was used, with 26 second-year elementary school students from a public municipal school in Ribeirão Preto/SP. Information collection was carried out through class diaries produced by the Physical Education teacher-researcher for 22 classes with a football theme. From data analysis, three categories were created, namely: a) more experienced player: being a teacher with expectations, difficulties and legal/bureaucratic attributions, which focuses on the analysis of the teacher who sought to innovate and develop her work within the CCEF , however, he came across his previous experiences that influence his classes; b) challenging players: being a child and creating their own paths and learning, which focuses on children who are also active actors in classes and challenge the teacher to think and constantly re-plan; c) playing with the Cultural Curriculum: the new one that comes from the Physical Education Cultural Curriculum, which highlights the space in which the different ones are found and delimits the rules of pedagogical work from the perspective of the CCEF. The work showed that difficulties were faced in creating this curriculum, given the contradictions and learning that occurred, on the part of the children and the teacher-researcher, during the process. From this pedagogical experience it was possible to learn more about how the CCEF materialized with a second-year class of elementary school and, from there, suggest that new studies be carried out so that we can increasingly know and recognize the Cultural Education Curriculum Physical.